Serum miRNA-186-3P and miRNA-382-3P constitute a novel Diagnostic miRNA signature for palindromic rheumatism - Yuan, Fangfang; Weng, Zefu; Yang, Qiong; Luo, Jing; Ying, Lina; Huang, Haiyan; Zhang, Xin; Chen, Yahui; Lin, Jixia; He, Junhong (Frontiers in Immunology, 2025)
BackgroundPalindromic rheumatism (PR) is a unique disease characterized by the intermittent inflammation of different joints that may progress to a variety of immune-related diseases. Unclear diagnostic criteria have limited the research on its pathogenesis and treatment options. Recently, microRNAs (miRNAs) have been used in the diagnosis of various diseases; however, the role of miRNAs in PR diagnosis remains unexplored. Using next-generation high-throughput sequencing (NGS), this study aimed to screen miRNAs specifically expressed in the serum of patients with PR to construct a miRNA signature and verify its diagnostic efficacy.MethodsPatients with PR (N=4), patients with rheumatoid arthritis (RA; N=3), and healthy individuals (Con; N=3) were included in an exploration cohort. Differentially expressed miRNAs were screened using NGS to construct a miRNA signature, and bioinformatics tools were used to perform target gene enrichment analysis of the top 25 differentially expressed miRNAs, both upregulated and downregulated. RT-qPCR was used to verify the differential expression of the miRNA signature in three validation cohorts of patients with PR (N=27) and RA (N=30), and healthy individuals (N=31). The efficiency of the miRNA signature was evaluated using receiver operator characteristic (ROC) curves, an analytical method that assesses diagnostic accuracy.ResultsA total of 130 miRNAs were differentially expressed in the PR exploration cohort, including 35 upregulated and 95 downregulated compared to levels in the RA and healthy cohorts. miRNA-186-3p showed the largest upregulated difference and miRNA-382-3p the largest downregulated difference; these were selected to construct the miRNA signature. In the ROC curve of the validation cohort, the PR miRNA signature produced an area under the ROC curve (AUC) of 0.980 (95% CI 0.942–1.000) when distinguishing from healthy individuals and of 0.906 (95% CI 0.830–0.983) when distinguishing from RA patients. However, miRNA-186-3p and miRNA-382-3p levels were not associated with disease activity in patients with PR.ConclusionA miRNA signature comprising miRNA-186-3p and miRNA-382-3p can effectively diagnose and differentiate PR from RA. This study provides a basis for the creation of a clinical miRNA signature for the diagnosis of PR.